Predominance of Mycobacterium tuberculosis EAI and Beijing Lineages in Yangon, Myanmar - Phyu, Sabai (American Society for Microbiology (ASM), 2009)
Isolates of the Mycobacterium tuberculosis Beijing lineage are associated with high rates of transmission, hypervirulence and drug resistance. The Beijing lineage has been shown to dominate the tuberculosis (TB) epidemic in East Asia; however, the diversity and frequency of M. tuberculosis genotypes from Myanmar are unknown. We present the first comprehensive study describing the M. tuberculosis isolates circulating in Yangon, Myanmar. Thus, 310 isolates from pulmonary TB patients from Yangon, Myanmar, were genotyped by spoligotyping and IS6110-based restriction fragment length polymorphism analysis (IS6110 RFLP). The most frequent lineages observed were the East African-Indian (EAI; 48.4%; n = 150) and Beijing (31.9%; n = 99) lineages. Isolates belonging to the most frequent shared types (STs), ST1 (n = 98; Beijing), ST292 (n = 28; EAI), and ST89 (n = 11; EAI), had ≥75% similarity in their IS6110 patterns. Five of 11 Beijing isolates comprising five clusters with identical IS6110 RFLP patterns could be discriminated by mycobacterial interspersed repetitive-unit-variable-number tandem-repeat (MIRU-VNTR) analysis. Of the 150 EAI isolates, 40 isolates (26.7%) had only one IS6110 copy, and 17 of these isolates could be discriminated by MIRU-VNTR analysis. The findings from this study suggest that although there is a predominance of the ancient EAI lineage in Yangon, the TB epidemic in Yangon is driven by clonal expansion of the ST1 genotype. The Beijing lineage isolates (21.4%) were more likely (P = 0.009) than EAI lineage isolates to be multidrug resistant (MDR) (1.3%; odds ratio, 3.2, adjusted for the patients' history of exposure to anti-TB drugs), suggesting that the spread of MDR Beijing isolates is a major problem in Yangon.